Preconception reflections, postconception intentions: the before and after of birth control in Australian adolescent females - Smith, Jennifer; Skinner, S; Fenwick, Jennifer (C S I R O Publishing, 2013)
Background: The relationship between pregnancy intentions and contraceptive behaviour is difficult to establish. This study explored the contraceptive histories of teenagers with a recent experience of pregnancy to generate qualitative profiles of pregnancy intentions. Subsequent intentions in relation to birth control were also examined. Methods: A purposive sample of female teenagers aged 14–19 years was recruited from various clinical and community-based antenatal and postnatal services and termination services across the Perth metropolitan area. The current analysis was based on a total of 56 semistructured interviews. A two-staged process of thematic analysis was conducted to identify commonalities emerging from the narrative data. Results: Three pregnancy intention profiles were identified: 1) unplanned, unwanted, unlikely; 2) planned, wanted, likely; and 3) unplanned, ambivalent, likely. Each profile represents variation in pathways to pregnancy based on teenagers’ accounts of pregnancy desires, personal responsibility over contraceptive use, and perceptions of pregnancy risk. Regardless of the way that pregnancy was resolved (i.e. termination or childbirth), similar postconception intentions surrounding birth control emerged through a shared discourse of pregnancy avoidance across the sample. Conclusions: Exploring adolescents’ understandings of the decisions and behaviours that lead to pregnancy will assist in the development of more accurate assessment tools to identify those at risk of unplanned and unwanted pregnancies. Our research also suggests that the provision of contraceptive counselling immediately after conception, followed by ongoing support, may help to maintain strong intentions to delay further pregnancies as identified in our study.